Rendimento de grãos, óleo e qualidade de sementes de híbridos de canola em diferentes espaçamentos e épocas de semeadura - Bazo, Gabriel Loli (2013)
In Brazil, the cultivation of canola tends to take high potential to biodiesel production, bran, alternative protein foods, and good quality vegetable oil. The goal of this research was to evaluate the yield potential, seed quality and oil and protein contents of four canola hybrids, which were subjected to two sowing dates in two different spacings in Maringá city- PR, during the harvest of 2011 and 2012. The experiment was conducted with 16 treatments in 2 sowing dates (04/08 and 05/10), 2 spacings (17 and 45 cm) and 4 hybrids (Hyola 76, Hyola 61, Hyola 433 and Hyola 411). The experimental design was a randomized complete block design with the treatments in a split-split plot design with four replications in the field. The yield potential of each hybrid was evaluated through productivity and oil production in kg ha-1 and the weight of a thousand seeds. Seed physiological quality was evaluated by means of germination, first count of germination, electric conductivity and accelerated aging. The chemical composition of the seeds was determined by the oil content and protein. Differences in climatic conditions between seasons affected the physiological quality of seeds. The cultivation of canola seed in northern Paraná is feasible according to the grains production. The hybrid canola Hyola 411 and 433 may be suitable for sowing in early May once that it presented a higher yield of oil production and grains. Hyola 61 can be recommended for planting in early April.